Translation Techniques Used in Monster University Movie - Yesintha Kristina, Ni Putu Tania; Widiastuti, Ni Made Ayu (e-Journal of Linguistics; Vol 15 No 2 (2021): en, 2021)
This article discussed the translation techniques that is used in the subtitle of the movie “Monster University”. This article used ten sentences that are found in the movie script of “Monster University” as the data source. Qualitative and descriptive methods were used to analyze the data. This article used the theory by Molina and Albir (2002) to find out the translation techniques used by the translator to translate the English movie script. The result of the analysis showed that there were eight translation techniques found in the data; adaptation (2 data), borrowing (1 data), established equivalent (2 data), generalization (1 data), linguistic amplification (1 data), linguistic compression (1 data), literal (1 data), and transposition (1 data).